Methylene Blue Removal by Chitosan Cross-Linked Zeolite from Aqueous Solution and Other Ion Effects: Isotherm, Kinetic, and Desorption Studies - Endar Hidayat; Seiichiro Yonemura; Yoshiharu Mitoma; Hiroyuki Harada (Adsorption Science & Technology)
Developing innovative technology for removing methylene blue (MB) from water is essential since the widespread discharge of MB from industrial effluents causes problems for humans and the environment. In this study, we conducted the adsorption method, a simple technique that utilizes an adsorbent. Chitosan is cross-linked with zeolite as a promising adsorbent material and environmentally friendly. For the characterization, FTIR, SEM-EDS, DLS, and pHzpc were analyzed. It was discovered that the removal percentage reached 97% with an adsorption capacity of 242.51 mg/g for 60 minutes at pH 10. The adsorption isotherm and kinetic model were investigated. As a result, the Freundlich model and pseudo-second-order model were fitted to the adsorption process. Moreover, the effect of other ions was investigated for 5 minutes of mixing time. The results showed that the removal percentage increased in the presence of H2O2 ion. Contrary to sodium chloride, glucose, and citric acid ions, the effectiveness of H2SO4 as a desorbing agent was 99.65% for 30 minutes at 45°C.